Fatigue crack growth behaviour and life prediction for 2324-T39 and 7050-T7451 aluminium alloys under truncated load spectra - Bao, Rui; Zhang, Xiang (Elsevier Science B.V., Amsterdam., 2010)
This paper presents a study of crack growth behaviour in aluminium alloys 2324- T39 and 7050-T7451 subjected to flight-by-flight load spectra at different low- stress truncation levels. Crack branching was observed in the higher truncation levels for the 2324 and in all truncation levels for the 7050. Mode I crack growth life can be predicted for the 2324 alloy by the NASGRO equation and the Generalised Willenborg retardation model. However, quantitative prediction of the fatigue life of a significantly branched crack is still a problem. Material properties, test sample’s orientation and applied stress intensity factor range all play dominant roles in the fracture proces
Keywords: Fatigue crack growth; Fatigue load spectra; Crack branching; Retardation; Life prediction